122 Anti-human papillomavirus antibody detection using rhodamine B labeled L1-HPV-16 derived peptides. (18th September 2019) - Torrado García, LM; Rincón-Orozco, B; Urquiza, M; Rodriguez, J; Jones-Cifuentes, N; Ortiz, C
Abstract : Objectives: To detect differences in anti-HPV antibodies response between young women HPV-vaccinated and unvaccinated using rhodamine-b labeled L1-derived peptides and non-conventional techniques. Methods: The peptides were designed from the epitopes of the virus surface recognized by the antibodies of B cells from HPV-infected. Serum from eight VLP vaccinated women, who have received three doses of immunization (positive controls PC), and serum from eight girls under 14 years of age, who have not had their first intercourse (negative controls NC), were obtained by venipuncture at the faculty of health of Universidad Industrial de Santander and at the university hospital. The fluorescence polarization assays were performed and the polarization readings were made in the microplate reader using a cube of filters for polarization with excitation wavelength of 525 nm and emission at 585 nm. These serum were also tested by Enzyme-linked immunosorbent assay (ELISA). Results: It was found that these designed peptides presented higher reactivity with antibodies from the serum of PC-women than with antibodies from the serum of NC-women with p <0.0001. Six out of eleven peptides derived from three L1-regions were specifically recognized by antibodies present in the serum of HPV-vaccine immunized women as was detected by ELISA. Peptide P-BC in the dot fluorescence assay showed the highest specific reactivity to PC-serum, suggesting that this peptide could be used to detect changes in the antibody response against HPV with this technique. Conclusions: Fluorescent peptides from the L1 protein can be used to detect of antibodies induced by vaccination using different techniques.